APPLYING UNIVERSAL DESIGN TECHNOLOGY IN LEARNING AT ISLAM RELIGIOUS EDUCATION STUDY PROGRAM AT ISLAMIC INSTITUTE OF ALMUSLIM ACEH - Mizwar, Edi; Saputra, Edi; Jannah, Miftahul (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2025)
This research aims to analyze the utilization of Universal Design technology in learning within the Islamic Education Study Program at Almuslim Islamic Institute in Aceh. The research methodology employs a qualitative approach with a case study design to understand the phenomena occurring in the Islamic Education Study Program at Almuslim Islamic Institute in Aceh. Research results show that the application of Universal Design for Learning (UDL) in religious education has great potential to enhance students' learning experiences by creating an inclusive environment that is responsive to diverse needs. This research explores the diversity of teaching methods that can enhance student engagement, such as project-based learning, the use of multimedia, and group discussions. However, challenges arise from the consistency of method implementation by instructors and the accessibility of technology, which can hinder student participation. Student involvement in curriculum development has also been identified as an important factor that can enhance motivation and the relevance of learning. By providing adequate training for educators, ensuring technology accessibility, and involving students in the learning process, educational institutions can create a more inclusive and effective learning experience. The results of this study indicate that the implementation of UDL not only improves students' learning outcomes but also prepares them to face challenges in an increasingly complex and diverse world.